On Certain Aspects of Class Ideology in the Ten Commandments (From the History of the Atheistic Thought in Lithuania in the Late 19th and the Early 20th Centuries) - Barzdaltis, Juozas (Problemos, 1973)
The Lithuanian atheists of the late 19th and the early 20th centuries rejected the supernatural origin of the Ten Commandments considering many of them to be characteristic of class society. They held that the famous commandments “Thou shalt not kill”, “Thou shalt not steal”, etc., are devoid of the absolute meaning attached to them by the clergy. The rule “Thou shalt not steal” prohibits only some forms of theft and does not apply to the exploitation of man by man. Although being right in a number of their theses, the Lithuanian atheists did not rise to a scientific understanding of the problem. They were unable to approach social phenomena historically and could not give a correct evaluation of the morals of the Decalogue under concrete historical conditions. Actually they reduced the polemics with the clergymen to the following question: was the morals propagated by religion good or bad, and was the behaviour of clergymen good or bad.